2024
DOI: 10.1002/anie.202319355
|View full text |Cite
|
Sign up to set email alerts
|

Lithiophilic Covalent Organic Framework as Anode Coating for High‐Performance Lithium Metal Batteries

Xinyu Wu,
Shuoqing Zhang,
Xiaoyi Xu
et al.

Abstract: The growth of disorganized lithium dendrites and weak solid electrolyte interphase greatly impede the practical application of lithium metal batteries. Herein, we designed and synthesized a new kind of stable polyimide covalent organic frameworks (COFs), which have a high density of well‐aligned lithiophilic quinoxaline and phthalimide units anchored within the uniform one‐dimensional channels. The COFs can serve as an artificial solid electrolyte interphase on lithium metal anode, effectively guiding the unif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Through a comparative analysis of the surface morphology of the electrode postcycling (Figure 3cf), the LZU1-COF layer demonstrates a significant capability in suppressing the proliferation of lithium dendrites. Similarly, Wu et al 115 synthesized COFs with polyimide organic functional groups, named HAHATN-PMDA-COF. It has a 2D triangular structure and a uniform one-dimensional channel (Figure 3g), which provides a way for Li + migration and greatly improves the amount of Li + migration like Figure 3h.…”
Section: Single Cofsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through a comparative analysis of the surface morphology of the electrode postcycling (Figure 3cf), the LZU1-COF layer demonstrates a significant capability in suppressing the proliferation of lithium dendrites. Similarly, Wu et al 115 synthesized COFs with polyimide organic functional groups, named HAHATN-PMDA-COF. It has a 2D triangular structure and a uniform one-dimensional channel (Figure 3g), which provides a way for Li + migration and greatly improves the amount of Li + migration like Figure 3h.…”
Section: Single Cofsmentioning
confidence: 99%
“…(h) Side view of a graphic presentation of HAHATN-PMDA-COF (nitrogen, blue; carbon, green; oxygen, red; hydrogen, white). Reprinted with permission from ref . Copyright 2024 Wiley-VCH.…”
Section: Cof-based Electrodesmentioning
confidence: 99%
“…While using nanoporous materials in batteries to suppress the growth of Li dendrites, 18,20,37–42 there has been great progress in inhibiting the side reactions between liquid electrolytes and the Li anode. The uniform nanoporous separator, designed and prepared by our group, not only prevented lithium dendrite formation over extended cycling periods in both Li–Li symmetric batteries and high-voltage lithium metal batteries that used LiNi 0.6 Mn 0.2 Co 0.2 O 2 as the cathode, but also effectively inhibited side reactions, allowing the Li anode to maintain its original metallic lustre.…”
Section: Nanoporous Materials In Batteriesmentioning
confidence: 99%
“…Conjugated polymers (CPs) are an important component of bulk-heterojunctional OPDs in which structure modification of CPs can adjust their molecular aggregation, charge transport, and optoelectronic properties. CPs possess unique semiconductor properties, and understanding how to control their optoelectronic performance is critical for designing CPs with improved photoresponse characteristics. A large number of studies in the field of organic electronics show that the halogenation strategy is an ideal method to improve the optoelectronic properties of CPs. Fluorine (F) substitution, in particular, can not only adjust the energy level structure of CPs but also improve their crystallinity, trap density, and mobility. Bai et al found that in D-A-type CPs, fluorination of electron-donating units can suppress density of trap states in the active layer, effectively enhancing performance of OPDs . Additionally, Park et al studied the effect of fluorinated alkyl chains in CPs on J dark and D* of OPDs.…”
Section: Introductionmentioning
confidence: 99%